PENGARUH DUKUNGAN ORGANISASI (ORGANIZATIONAL SUPPORT) TERHADAP KINERJA PEGAWAI (EMPLOYEE PERFOMANCE) DI LEMBAGA PEMASYARAKATAN KELAS IIA BANYUASIN - Faikar, Nurrahman Putra; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2024)
This research aims to determine the influence of organizational support on employee performance at the Class IIA Banyuasin Correctional Institution. The research method used is quantitative research with a nonexperimental quantitative design by testing causal relationships (Causality-Comparative Research). The population used was all 85 employees. This research uses a sampling technique with total sampling. Data was obtained from the results of the questionnaire. Data analysis used univariate analysis, normality test, simple linear regression, significance test and determination test using IBM SPSS 25 software. The results of the study showed that there was a positive and directly proportional influence between variable X and variable. The R square value is 23.1 which shows that organizational support is 23.1% influenced by existing performance and the remaining 76.9% is influenced by other variables. There is a positive influence of organizational support on employee performance at the Class IIA Banyuasin Correctional Institution. Keywords: Organizational Support; Employee Performance; Correctional Institutions